2018
DOI: 10.2196/medinform.7170
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Decision Support in Computerized Provider Order Entry: Systematic Literature Review

Abstract: BackgroundComputerized decision support systems have raised a lot of hopes and expectations in the field of order entry. Although there are numerous studies reporting positive impacts, concerns are increasingly high about alert fatigue and effective impacts of these systems. One of the root causes of fatigue alert reported is the low clinical relevance of these alerts.ObjectiveThe objective of this systematic review was to assess the reported positive predictive value (PPV), as a proxy to clinical relevance, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…They also proposed tiering of alerts to improve acceptance and consideration of human factors in CDS design [20] The analytic reviews analyzed the features of previously implemented CDS tools. Several reviews examined alert use, generally finding acceptance rates to be low [21] and override rates to be high [22][23][24]. Hussain et al delved into why alerts are so commonly overridden and found that although interruptive alerts are the most common design, they are also the least accepted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also proposed tiering of alerts to improve acceptance and consideration of human factors in CDS design [20] The analytic reviews analyzed the features of previously implemented CDS tools. Several reviews examined alert use, generally finding acceptance rates to be low [21] and override rates to be high [22][23][24]. Hussain et al delved into why alerts are so commonly overridden and found that although interruptive alerts are the most common design, they are also the least accepted.…”
Section: Resultsmentioning
confidence: 99%
“…Carli et al undertook a systematic review of positive predictive values (PPVs) of CDS alerts as a proxy for clinical relevance, finding massive PPV variations from 0% to 97%, with most in the 20%-40% range. PPVs were higher when the contextual information of the individual patient was considered in CDS, so the authors concluded that incorporating as much specific patient data as possible to improve PPV is more important than using a large database of knowledge that may generate many false positives and thus promote alert fatigue [24]. In a systematic review to understand CDS for drug allergies, Légat et al found that significant inaccuracies in the EHR due to the difficulty of structured documentation of allergies, the lack of standard allergy terminology, and irregular updating of allergy databases resulted in poor specificity and overall performance of CDS allergy alerts, along with override rates of up to 90%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern commonly occurs, with a recent review reporting the "positive predictive value" of such alerts ranging from 8 to 83%. 24 We considered the following five potential explanations in our setting:…”
Section: Discussionmentioning
confidence: 99%
“…EHR alerts and dosing guidance might encourage appropriate dosing. However, alert fatigue has led many health systems to either deactivate electronic health record (EHR) drug alerts or display only the highest-risk alerts [18,19]. Additionally, many of the DOAC dosing issues may develop after the initial prescription (e.g., progressive renal function decline, failure to change VTE lead-in dosing for apixaban or rivaroxaban after 7 or 21 days, respectively) [20,21].…”
Section: Introductionmentioning
confidence: 99%